System identification and adaptive control of micro helicopter. Issue 1 (February 2021) - Xu, Weixiong; Zhang, Fubiao; Lin, Defu
Abstract: This paper copes with the controller design problem of a micro helicopter, which is a multivariable and strongly coupled nonlinear system. The state-space model near the hovering condition of pitch and roll channels is acquired by least-square system identification method, with flight test verification. Based on the identified model, model reference adaptive control is designed as angular rate controller, and PID controller is used to stabilize attitude loop. State-space model helps to decouple the roll and pitch channels, and model reference adaptive control can address external disturbances, model uncertainties and nonlinearities of the dynamics, which can be estimated and further eliminated online. Eventually, both simulations and actual flight tests are conducted to verify the effectiveness of the proposed control scheme.